An Integrative Review of Engineering Ethics Education at Delft University of Technology: Contexts, Assumptions, and Practices. - M. Phoenix, Daniel; Zhu, Qin; Gammon, Andrea; Clancy, Rockwell (Science & Engineering Ethics, 2026)
Engineering ethics education has undergone significant development across institutions worldwide over the last three decades. While earlier analyses have examined aspects of this development, few integrated accounts have traced the evolution of a leading institution’s approach to engineering ethics education across this period. This paper addresses this gap. It presents an integrative review of engineering ethics education at Delft University of Technology (TU Delft), one of Europe’s most influential institutions in this field. Drawing on peer-reviewed articles, books, book chapters, conference papers, and institutional documents published by TU Delft scholars over three decades, we trace the historical development of the institution’s approach, analyze its core theoretical assumptions and examine its learning goals and evolving pedagogical practices. The review identifies two distinct stages in the institution’s development. It reflects a deepening of learning goals and, most notably, a shift toward experiential and non-cognitive pedagogical approaches. These findings offer a reference point for discussing how ethics should be taught to engineers, how to integrate it into technical curricula, and which kinds of normative stances institutions should adopt in their ethics programs.